Strategies For FPGA Implementation Of Non-Restoring Square Root Algorithm - Sutikno, Tole; Jidin, Aiman Zakwan; Jidin, Auzani; Nik Idris, Nik Rumzi (Institute of Advanced Engineering and Science, 2014)
-